Firm Value dan Faktor Penentunya di Sektor Energi: Peran Strategis Komisaris Independen - Rosalina; Waskito, Jaka; Utami, Yuni (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The determination of firm value in the energy sector is influenced by internal performance and the effectiveness of corporate governance. This study aims to examine the determinants of firm value Return on Assets (ROA), Total Asset Turnover (TATO), and Debt to Equity Ratio (DER) and to assess the strategic role of Independent Commissioners as a governance mechanism in moderating these relationships. Using a quantitative approach and secondary data from the financial reports of 36 energy companies listed on the Indonesia Stock Exchange during 2020–2024, the analysis employed multiple linear regression and moderation regression techniques. The results show that ROA (β = 0.739; p = 0.001), TATO (β = 0.488; p = 0.000), and DER (β = 0.026; p = 0.001) have a significant positive effect on firm value. However, Independent Commissioners negatively moderate the effect of ROA (β = -6,687; p = 0,006) and DER (β = -0,301; p = 0,002) on firm value, and do not significantly moderate the effect of TATO (β = 0,505; p = 0,302). These findings suggest that the strategic role of Independent Commissioners in supporting firm value has not yet been fully effective in Indonesia’s energy sector.